2008
DOI: 10.4314/sjms.v3i1.38512
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Selenium, Zinc, Copper and Magnesium in Asthmatic Patients: a Case Control Study.

Abstract: Background: Free radicals have harmful effects on cells and tissues and are thought to be responsible for the pathogenesis of many diseases including bronchial asthma. Selenium (Se), Zinc (Zn), copper (Cu), and magnesium (Mg) are trace elements required for the antioxidant enzymes and hence the optimal functions of the immune system. Changes in the levels of these elements may lead to a reduction in antioxidant activities in asthma.Objective: This study was conducted to determine serum levels of the trace elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Thus, twenty-two articles with twenty-six studies provided results for Zn level (5,7,8,10,(12)(13)(14)(15)(16)(17)(25)(26)(27)(30)(31)(32)(33)(34)(35)(36)(37)(38) and twenty-four articles with forty studies provided results for Se level (5,(9)(10)(11)13,16,25,28,29,31,32,35,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) . The detailed characteristics of the included studies are shown in the online supplementary material, Supplemental File S1 for Zn and Supplemental File S2 for Se.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, twenty-two articles with twenty-six studies provided results for Zn level (5,7,8,10,(12)(13)(14)(15)(16)(17)(25)(26)(27)(30)(31)(32)(33)(34)(35)(36)(37)(38) and twenty-four articles with forty studies provided results for Se level (5,(9)(10)(11)13,16,25,28,29,31,32,35,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) . The detailed characteristics of the included studies are shown in the online supplementary material, Supplemental File S1 for Zn and Supplemental File S2 for Se.…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup analyses and meta-regressions with the covariates of several study and population characteristics did not successfully explain the heterogeneity. The further 'leave-one-out' sensitivity analyses using I 2 > 50 % as the criterion suggested that six studies (7,8,10,17,25,38) in Zn analysis and seven studies (10,11,35,38,42,45,47) in Se analysis contributed to the high between-study heterogeneities. After excluding these studies, no significant association of Se with asthma was found, which needs to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations